The Contribution of Sundanese Ulama in the Maintenance of Pegon Script as an Islamic Intellectual Tradition in Indonesia - Dedi Supriadi; Moeflich Hasbullah; Faisal Muhmoud Adam (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2026)
Although traditional Muslim scholars in the Nusantara (the Malay-Indonesian archipelago) have been widely studied for their roles in religious propagation, politics, and education, their contributions to the development of indigenous writing traditions remain insufficiently explored. Among the most significant yet understudied of these contributions is the Pegon script, an adaptation of Arabic letters systematically modified to transcribe local languages such as Sundanese and Javanese, which served as a primary vehicle for the production and transmission of Islamic knowledge across the region. Existing scholarship on Pegon manuscripts has predominantly concentrated on philological editing and textual criticism, while the role of Muslim scholars in shaping Pegon as a dynamic medium for transmitting Islamic knowledge and constructing cultural identity has received comparatively limited attention. This study employs historical and philological approaches, combined with critical discourse analysis, to examine Sundanese manuscripts written in the Pegon script, drawing on local historical narratives and archival sources. The findings demonstrate that Pegon functioned not merely as a writing system but as a multidimensional intellectual instrument: a pedagogical medium within ulama and pesantren networks, a cultural bridge connecting local and global Islamic traditions, and a subtle instrument of resistance to colonial authority. Taken together, these findings attest to the remarkable intellectual creativity of Sundanese ulama in developing an effective vernacular writing system and underscore the critical importance of manuscript studies in reconstructing the dynamics of Islamic intellectual history in Southeast Asia.